An Exploration Into the Importance of a Sense of Belonging for Online Learners - Peacock, Susi; Cowan, John; Irvine, Lindesay; Williams, Jane (International Review of Research in Open and Distributed Learning, 2020)
Fostering a sense of belonging and a personal connection is seen as fundamental by many educational researchers, regardless of the learning environment. Online learning certainly provides flexible learning opportunities but comes with notable issues. For online learners, nurturing a sense of belonging may present a way of improving their experiences and attainment, as well as reducing attrition rates. Research specifically exploring sense of belonging and online learning is limited. This article addresses that gap and reports on a small-scale exploratory study using qualitative data-collection and analysis methods to investigate the importance, or not, of sense of belonging for postgraduates’ online education by exploring the origins and nature of their lived experience of online learning and their sense of belonging therein. Our initial findings emphasise its importance for them as online learners and have identified three significant themes: interaction/engagement, the culture of the learning, and support. These early findings highlight the importance of these three themes in promoting a sense of belonging and in ensuring that there are opportunities for meaningful group and peer interactions; they will be of interest to all engaged in online education.